Ecological sustainability in social housing delivery: A path towards a greener future in South Africa. - Makalima, Mzuchumile (Acta Carolus Robertus, 2024)
The provision of sustainable social housing in South Africa emerges as a pivotal challenge within the context of rapid urbanization and historical housing disparities. This article examines the integration of ecological sustainability principles into social housing delivery through a qualitative approach. An analysis of diverse case studies highlights the successful implementation of green building design, renewable energy integration, water management strategies, biodiversity preservation, and waste reduction initiatives. These practices contribute to energy savings, reduced environmental footprints, and improved resident well-being. Furthermore, insights from expert interviews illuminate the motivations driving sustainability integration, including government policies, and growing awareness among developers and communities. Nonetheless, challenges such as initial costs, regulatory complexities, and community resistance underscore the complexity of the endeavor. Government policies, community engagement, and collaboration between stakeholders emerge as pivotal drivers of sustainable social housing. By balancing economic viability, environmental responsibility, and social inclusivity, South Africa can navigate its housing crisis while creating urban environments that are both ecologically sound and socially equitable.